BENCHMARKING ANALYSIS FOR SALAK-BASED PROCESSED PRODUCT DEVELOPMENT STRATEGY AT UD. BOLU SALAK KENANGA IN PADANGSIDIMPUAN CITY - Riyahul Jannah; Suryadi; Wahyu Isnanda Nasution (Jurnal Mahasiswa Agribisnis, 2026)
UD. Salak Kenanga is a business that produces processed salak products located in Ujung Padang Village, Padangsidimpuan Selatan District, South Tapanuli Regency. Salak processed production at UD. Bolu Salak Kenanga is not yet widely known by the public and the product innovation produced is still minimal, especially in terms of variants. In addition, the promotion carried out has not been optimal so that the income obtained is still low. This study aims to benchmark against similar competitors to find competitive advantages, then formulate a development strategy using SWOT and QSPM analysis. The research method used is a qualitative approach by processing data starting with the input stage, matching stage, and decision-making stage. Based on the results of the IFE and EFE matrix analysis, it shows that UD. Bolu Salak Kenanga is in quadrant I which focuses on the SO (Strength-Opportunity) strategy and produces 3 alternative strategies. The results of the QSPM matrix show that the main priority strategy is to strengthen the branding of innovative MSMEs with the support of technology and partnerships with the government and MSMEs with a TAS score of 4.27.